Capacity Building for Poncokusumo Farmers and Malang Raya Coffee Enthusiasts toward Quality Standardization - Sunarharum, Wenny Bekti (Journal of Innovation and Applied Technology, 2025)
Focus Group Discussions (FGD), technical guidance, training, mentoring, and evaluation. Training materials cover coffee cultivation based on Good Agricultural Practices (GAP), post-harvest processing, coffee quality and sensory analysis, financial and business management using the Business Model Canvas (BMC), and digital marketing strategies through website creation and QR codes. Results show increased participant understanding, proven by post-test scores. Farmers gained practical knowledge from cultivation to marketing, while coffee enthusiasts improved their capacity in sensory evaluation. The outputs include scientific journals, national seminars, media publications, modules, and Intellectual Property Rights (IPR). Overall, the program effectively enhanced the skills and knowledge of coffee stakeholders in the target area, supporting the development of high-quality, market-competitive Malang coffee. This program supports the achievement of SDG 8 (Decent Work and Economic Growth) and SDG 12 (Responsible Consumption and Production).